2007
DOI: 10.1182/blood-2007-01-070284
|View full text |Cite
|
Sign up to set email alerts
|

Impaired responsiveness to T-cell receptor stimulation and defective negative selection of thymocytes in CCR7-deficient mice

Abstract: The chemokine receptor CCR7 has been implicated in maintenance of thymus morphology and establishment of tolerance to self-antigens. In this study, we provide direct evidence that negative selection of maturing thymocytes is defective in CCR7-deficent mice. Impaired negative selection was observed after TCR/CD3 complex stimulation in vivo as well as in vitro and was prominent in both doublepositive and semimature single positive cells (CD4 ؉ CD8 ؊ CD24 high ). It is noteworthy that thymocytes of CCR7 ؊/؊ mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 39 publications
5
58
1
Order By: Relevance
“…These results indicate that CCR7 directs the migration of SP thymocytes to the medulla. However, a recent report by DavalosMisslitz et al (15) showed that the density of CD4SP thymocytes in the medulla was not reduced in thymus sections of CCR7 Ϫ/Ϫ (ML) mice, thereby questioning the role of CCR7 in the migration of SP thymocytes to the medulla. Accordingly, we reexamined whether CCR7 contributes to the migration of thymocytes to the medulla.…”
Section: Ccr7 Is Required For the Migration Of Positively Selected Thmentioning
confidence: 97%
“…These results indicate that CCR7 directs the migration of SP thymocytes to the medulla. However, a recent report by DavalosMisslitz et al (15) showed that the density of CD4SP thymocytes in the medulla was not reduced in thymus sections of CCR7 Ϫ/Ϫ (ML) mice, thereby questioning the role of CCR7 in the migration of SP thymocytes to the medulla. Accordingly, we reexamined whether CCR7 contributes to the migration of thymocytes to the medulla.…”
Section: Ccr7 Is Required For the Migration Of Positively Selected Thmentioning
confidence: 97%
“…GIT2 − / − DP cells are hyper-responsive to chemotactic cues, which bias localization in the cortex, leading to perturbations in the positive selection process 12 . CCR7-deficient mice develop autoimmunity because of defective negative selection [13][14][15][16] . However, the mechanisms by which thymocyte trafficking controls these selection processes are not well understood.…”
mentioning
confidence: 99%
“…Despite being highly mobile (7), DP thymocytes remain sequestered in the cortex in frequent physical association with thymic epithelial cells (TECs), moving toward the thymic medulla via chemokine guidance only subsequent to TCR stimulation by self-derived peptide/MHC complexes (pMHC) that induce CD69 expression and support cell survival, i.e., positive selection (8,9). CD69 + DP cells differentiate further into CD4 + CD8 − or CD4 − CD8 + singlepositive (SP) thymocytes, translocating to the thymic medulla to complete their maturation (10,11). While traversing the thymus, immature αβ TCR + thymocytes that are strongly self-reactive with pMHC displayed on cortical and medullary TECs (cTECs and mTECs, respectively) are purged from the repertoire before peripheral exportation in a process termed negative selection (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%